Pengaruh Profitabilitas dan Pengungkapan Biaya Lingkungan Terhadap Kinerja Lingkungan - Eko Wiji Pamungkas; Dini Fitriani; Srie Hendraliany; Walda Hamidah; Dewi Melia; Dewi Sri; Melinda Ayu (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
. Environmental issues have become a concern in various industries, especially in mining companies, with the increasing environmental damage caused by their operational activities. Companies tend to focus on profit generation without considering the negative impacts arising from their operational activities. Allocating environmental costs can reduce repair costs arising from environmental damage and can increase competitive advantage through good environmental performance. This study aims to analyze the effect of profitability and environmental cost disclosure on corporate environmental performance. In the data processing process, this study used 24 samples from mining companies in Indonesia. The partial regression results show that profitability and environmental cost disclosure have no effect on environmental performance, but profitability and environmental cost disclosure simultaneously have an effect on environmental performance.